Gender differences in risk aversion: Do single-sex environments affect their development? (2014)
Single-sex classes within coeducational environments are likely to modify students' risk-taking attitudes in economically important ways. To test this, we designed a controlled experiment using first year college students who made choices over real-stakes lotteries at two distinct dates. Students were randomly assigned to weekly classes of three types: all female, all male, and coeducational. They were not allowed to change group subsequently. We found that women are less likely to make risky choices than men at both dates. However, after eight weeks in a single-sex class environment, women were significantly more likely to choose the lottery than their counterparts in coeducational groups. These results are robust to the inclusion of controls for IQ and for personality type, as well as to a number of sensitivity tests. Our findings suggest that observed gender differences in behaviour under uncertainty found in previous studies might partly reflect social learning rather than inherent gender traits